Medical Comorbidities as the Independent Risk Factors of Severe Adenovirus Respiratory Tract Infection in Adults - Wang Chun Kwok; Isaac Sze Him Leung; James Chung Man Ho; David Chi Leung Lam; Mary Sau Man Ip; Shuk Man Ngai; Kelvin Kai Wang To; Desmond Yat Hin Yap (Microorganisms)
Adenovirus is an important respiratory virus that causes severe diseases in immunocompromised patients. Data on its impact in immunocompetent patients are relatively limited. We conducted a territory-wide retrospective study on adult patients hospitalized for respiratory tract infections caused by adenovirus or influenza viruses in Hong Kong between 1 January 2016 and 30 June 2023. Inpatient mortality, severe respiratory failure (SRF), secondary bacterial pneumonia and acute kidney injury (AKI) were compared. The risk factors for these outcomes in patients hospitalized for adenovirus respiratory tract infections were assessed. Overall, 41,206 and 528 patients were hospitalized for influenza and adenovirus respiratory tract infections, respectively. Patients with respiratory tract infections due to adenoviruses showed significantly higher risk of inpatient mortality, SRF, secondary bacterial pneumonia and AKI compared to seasonal influenza. Medical comorbidities including cardio-pulmonary diseases, end-stage kidney disease requiring dialysis, and a lower estimated glomerular filtration rate were robust independent risk factors for inpatient mortality and serious respiratory outcomes in adenovirus respiratory tract infections. Adults hospitalized for adenoviruses respiratory tract infections had a significantly higher risk of inpatient mortality and adverse outcomes than adults infected with seasonal influenza. Medical comorbidities are important risk factors for severe adenovirus infections in adult patients.